Influence of flexible molecular structure on the cryogenic mechanical properties of epoxy matrix and carbon fiber/epoxy composite laminate. (October 2020) - Li, Shichao; Chen, Duo; Yuan, Yuhuan; Gao, Chang; Cui, Yunguang; Wang, Hongyu; Liu, Xin; Liu, Minjing; Wu, Zhanjun
Abstract: In this study, a flexible polymer (polysiloxane) containing SiOSi molecular chains and epoxy groups (EPSE) was prepared. The effect of EPSE on the cryogenic mechanical properties of epoxy matrix and carbon fiber (CF) reinforced epoxy composite laminate was investigated in detail. At RT, with an EPSE content of 8 wt%, the failure strain and fracture toughness KIC value of epoxy resin was improved by 69.4% and 10.4%, respectively. At cryogenic temperature, the tensile strength, failure strain and KIC value of EPSE-epoxy reached a maximum of 207 MPa, 3.13%, and 2.60 MPa·m 1/2, respectively. Micro-morphology of the fracture surface indicated that the incorporation of EPSE improved the resistance to crack growth. The flexural strength of CF/EPSE-epoxy laminate at 77 K was 17.2% higher than that of CF/neat epoxy laminate, which mainly attributed to the flexible SiOSi molecular chains in EPSE reducing the CF/matrix interface thermal stress. The transition of failure mode resulted in the jagged-shape load fluctuations in the load-displacement curves of laminates at 77 K. Thermal cycling affecting the flexural strength of CF/EPSE-epoxy laminate was mainly ascribed to the release of part of thermal residual stress and the formation of interface debonding. Graphical abstract: Unlabelled Image Highlights: A flexible polymer containing epoxy groups was prepared by the co-hydrolytic condensation reaction. The influence of flexible molecular chain on the cryogenic mechanical properties of epoxy and laminate was investigated. The flexural failure mode of carbon fiber/epoxy laminate at cryogenic environment was analyzed. The flexural strength of carbon fiber/epoxy laminate showed a peak value as the number of thermal cycles increased.